Endophytic bacteria enhance macrophyte resilience but reduce microbial network stability under eutrophication - Hao, Beibei; He, Bin; Zhang, Siyi; Wu, Haoping (Ecological indicators, 2025)
[Display omitted] •Species-specific morphological and physiological adaptations of submerged macrophytes to nutrient enrichment.•Functional shifts in endophytic bacteria from nutrient acquisition to stress resistance under eutrophication.•Trade-offs between enhanced macrophyte resilience and reduced microbial community stability under eutrophication. Lake eutrophication poses a serious threat to the biodiversity and ecosystem functions of submerged macrophytes. As symbiotic microorganisms of submerged macrophyte, endophytic bacteria can enhance plant’s stress resistance and promote its growth. However, whether they can help submerged macrophytes cope with eutrophication is not yet clear. This study investigated the interactions between submerged macrophytes and endophytic bacteria in eutrophic lakes, with a particular focus on their response mechanisms to eutrophication stress. The results show that resistant species, such as Myriophyllum spicatum, alleviate eutrophication stress by increasing proline accumulation and enhancing morphological complexity. In contrast, sensitive species like Hydrilla verticillata exhibited significant declines in key metabolic compounds. As nutrient level increases, the community of endophytic bacteria shifts from acquiring nutrients to resisting stress, and this shift is accompanied by a decrease in community network complexity and stability, which potentially reduce the long-term resilience of lake ecosystems. This study highlights the importance of submerged macrophyte-endophyte interactions in mitigating the eutrophication impacts, providing valuable insights for the restoration of degraded aquatic ecosystems.